2006
DOI: 10.1016/j.cell.2006.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Human mRNA Export Machinery Recruited to the 5′ End of mRNA

Abstract: Pre-mRNAs undergo splicing to remove introns, and the spliced mRNA is exported to the cytoplasm for translation. Here we investigated the mechanism for recruitment of the conserved mRNA export machinery (TREX complex) to mRNA. We show that the human TREX complex is recruited to a region near the 5' end of mRNA, with the TREX component Aly bound closest to the 5' cap. Both TREX recruitment and mRNA export require the cap, and these roles for the cap are splicing dependent. CBP80, which is bound to the cap, asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
481
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(531 citation statements)
references
References 63 publications
(123 reference statements)
38
481
1
2
Order By: Relevance
“…), this hypothesis remains to be tested in planta. In addition, our speculation is supported by the finding that the human transcription/export (TREX) complex, which is comprised of the core THO complex, is recruited to a region near the 59 end of the mRNA and that TREX recruitment requires the 59 cap (Sträßer et al 2002;Cheng et al 2006).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…), this hypothesis remains to be tested in planta. In addition, our speculation is supported by the finding that the human transcription/export (TREX) complex, which is comprised of the core THO complex, is recruited to a region near the 59 end of the mRNA and that TREX recruitment requires the 59 cap (Sträßer et al 2002;Cheng et al 2006).…”
Section: Discussionmentioning
confidence: 51%
“…SE encodes a zinc finger protein that has been implicated in mRNA splicing (Prigge and Wagner 2001;Laubinger et al 2008). Interestingly, some functions of the THO complex are dependent on splicing, and studies in animals have indicated that the THO complex interacts with the spliceosome (Rappsilber et al 2002;Zhou et al 2002;Masuda et al 2005;Cheng et al 2006). To determine whether EMU as well as SE are involved in mRNA splicing, we characterized the splicing patterns in emu mutant plants by examining transcripts of genes encoding serine/arginine-rich (SR) proteins, which belong to a conserved family of splicing regulators in eukaryotes and are extensively alternatively spliced (Reddy 2007;Long and Caceres 2009).…”
Section: Splicing Defects In Emumentioning
confidence: 99%
“…In mammals, the TREX complex is recruited primarily to the 5 0 end of transcripts through cooperative action of the nuclear cap-binding complex and the spliceosome [16,17]. Once bound to the mRNA, the TREX complex promotes nuclear export of fully processed transcripts through the nuclear pore by direct interactions between the TREX component, Aly, and the nuclear export factor, TAP-p15 [18,19].…”
Section: Splicing Directs Mrnp Formationmentioning
confidence: 99%
“…In addition to genes of unknown biochemical function, known FLC regulators include chromatin modifying enzymes, transcription factors, and a number of RNA-associated proteins, including ABSCISIC ACID HYPERSENSITIVE1 (ABH1; Hugouvieux et al, 2001;Bezerra et al, 2004). ABH1 encodes the plant homolog of CAP-BINDING PROTEIN80, a component of the nuclear cap-binding complex that has been implicated in pre-mRNA processing and nuclear export via the nuclear pore complex (NPC; Cheng et al, 2006).…”
mentioning
confidence: 99%